2016
DOI: 10.18520/cs/v111/i5/890-894
|View full text |Cite
|
Sign up to set email alerts
|

Full-Length Cloning and Characterization of Abiotic Stress Responsive <i>CIPK31-Like</i> Gene from Finger Millet, a Drought-Tolerant Crop

Abstract: Regulatory proteins such as protein kinases are known to play a crucial role in plant stress acclimation pathways. In this study, we report the identification and characterization of an abiotic stress responsive protein kinase called CBL Interacting Protein Kinase (EcCIPK31-like) from finger millet, a drought-tolerant crop. PCR-based approach was followed to clone 1350 bp coding region that encodes a 449 amino acid protein with a calculated molecular mass of 50.69 kDa. The conserved domain analysis revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Because CIPK31 inhibits both RBOHA and CatC and promotes ROS levels, further genetic study with a combination of rboha × catc will be interesting to dissect the mechanism of CIPK31‐mediated ROS homeostasis. Taken together, CIPK31 confers resistance to ShB (Figures 1a–f and 2a–e ), rice blast (Lin et al, 2021 ), and bacterial blight (Figure S2e–h ), and plays roles in growth and development in plants (Cho et al, 2019 ; Nagarjuna et al, 2016 ; Peng et al, 2018 ; Piao et al, 2010 ). However, clearly, CIPK31 interacts with CatC to modulate ROS homeostasis to promote rice resistance.…”
Section: Discussionmentioning
confidence: 93%
“…Because CIPK31 inhibits both RBOHA and CatC and promotes ROS levels, further genetic study with a combination of rboha × catc will be interesting to dissect the mechanism of CIPK31‐mediated ROS homeostasis. Taken together, CIPK31 confers resistance to ShB (Figures 1a–f and 2a–e ), rice blast (Lin et al, 2021 ), and bacterial blight (Figure S2e–h ), and plays roles in growth and development in plants (Cho et al, 2019 ; Nagarjuna et al, 2016 ; Peng et al, 2018 ; Piao et al, 2010 ). However, clearly, CIPK31 interacts with CatC to modulate ROS homeostasis to promote rice resistance.…”
Section: Discussionmentioning
confidence: 93%
“…Two abiotic stress responsive TFs belonging to bZIP family ( EcbZIP60 ) ( Babitha et al, 2015a ) and Basic helix-loop-helix (bHLH) family ( EcbHLH57 ) ( Babitha et al, 2015b ) were identified in GPU-28 genotype of finger millet under drought, osmotic, salt and methyl viologen (MV) stresses. Nagarjuna et al (2016) identified and characterized CBL interacting protein kinase31 ( EcCIPK31- like) gene responsible for drought tolerance in finger millet. A TATA box Binding Protein (TBP)- Associated Factors (TAFs) gene ( EcTAF6 ) was identified in GPU-28 genotypes of finger millet under drought stress ( Parvathi and Nataraja, 2017 ).…”
Section: Functional Characterization Of Key Genesmentioning
confidence: 99%